G86(P) Clinical Phenotype associated with recessive mutations in LARS gene. (7th April 2014) - Slattery, S; Casey, J; Lynam-Lennon, N; Mc Gettigan, P; O'Sullivan, J; Mc Dermott, M; Forde, K; Knerr, I; Treacy, E; Monavari, AA; Hughes, J; Bourke, B; et al.
Abstract : Our study involves 8 individuals (0.3–34 yrs) from 6 Irish Traveller families with intermittent liver dysfunction; 4 presented with acute liver failure in infancy. Additional features include chronic microcytic anaemia, developmental delay, and poor growth. During intercurrent febrile illnesses, hepatic decompensation (7/8) and encephalopathy with complex seizures are observed. Two patients died following viral infections; the eldest patient's worst decompensation was triggered by measles aged 4. The youngest patient was diagnosed at 4 weeks of age when he presented with poor tone, low birth weight, poor growth and a positive family history, hepatopathy subsequently developed at 2 months of age. Liver biopsies showed micro and macrosteatosis. Marrow erythroblasts have abnormal iron distribution. Extensive metabolic, genetic and mitochondrial investigations were negative. Exome sequencing has identified leucyl-t RNA synthetase (LARS) as the causative gene. Subsequent testing identified anothe Irish traveller patient who presented at 2 years with status epilepticus and a history of liver dysfunction and anaemia. He had acute Leigh like changes on MRI brain which resolved on follow up. Due to the multisystem nature of this disorder an underlying mitochondrial disorder had been suspected clinically, however knockdown of LARS in HEK293 cells did not impact on mitochondrial function sugesting that the hepatopathy is not primarily due to mitochondrial dysfunction. This in in keeping with the negative mitochondrial investigations. Recently, LARS was shown to activate mTORC1 which regulates autophagy, a process implicated in liver disease and host response to infections raising the possibilty that defective autophagy may be the underlying disease mechanism. Since our discovery, 2 further patients (non-Irish descent) with mutations in LARS have been identified at 2 US centres, reaffirming the cardinal clinical features of this disorder: poor infantile growth, microcytic anaemia, hepatopathy, decompensation and seizures with minor illness. In Ireland, LARS mutations should be suspected particularly in patients from the traveller population who present with liver dysfunction.